2008
DOI: 10.1007/s10867-008-9086-z
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Cells Grown and Baked on a Functionalized Mica Surface

Abstract: We demonstrate the cultivation of diatom cells on a functionalized mica surface and the preparation of frustules on a mica surface by baking. Diatom cells were successfully grown on a mica surface treated with 3-aminopropyltriethoxysilane. After baking at 400˚C for 2 h, frustule structures without the organic components of the diatom cells were successfully observed by scanning electron microscopy and atomic force microscopy. Furthermore, the frustules deformed and became slender when a sample was baked at 800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…In order to analyze by optical or electron microscopy the morphology of their surface, organic matter must be removed by proper cleaning protocol. High temperatures, i.e., baking rough material at 400–800 °C can be used; the procedure, generally used in industrial applications, has the disadvantage that can close the micropores and damage the original architecture of frustules . An alternative approach is a mixture of different acids.…”
Section: Bioderived Nanostructured Silicamentioning
confidence: 99%
“…In order to analyze by optical or electron microscopy the morphology of their surface, organic matter must be removed by proper cleaning protocol. High temperatures, i.e., baking rough material at 400–800 °C can be used; the procedure, generally used in industrial applications, has the disadvantage that can close the micropores and damage the original architecture of frustules . An alternative approach is a mixture of different acids.…”
Section: Bioderived Nanostructured Silicamentioning
confidence: 99%
“…Losic et al [8] tested the hardness and elastic modulus of two types of frustules using atomic force microscopy (AFM) and found that the cribellum, cribrum and girdles have different mechanical properties, and the elastic modulus of frustule is similar to that of porous silicon manufactured by anodic oxidation. Umemura et al [38] found that the structure and pores deform after heating at 800°C for 2 h. The frustule reacts with hydrofluoric acid and strong alkali [39,40], and thus it is compatible with silicon processing technology, such as wet etching, LIGA micromachining and silicon bonding [41,42].…”
Section: Materials Properties Of Diatom Frustulesmentioning
confidence: 99%
“…Compared with baking [38] and alkali etching, HF etching is a faster and cleaner method for pore enlargement and structure modification. (ii) Structural modification based on the natural methods of frustule formation: the formation of frustules in diatom cells is a bottom-up process.…”
Section: Structural Modification Of Diatom Frustulementioning
confidence: 99%
See 1 more Smart Citation
“…Losic 等人 [7] 通过原子力显微镜(AFM)对壳体的硬度 和弹性模量进行测试, 发现壳体棘孔、孔室、实心壳 片区域力学性能存在差异, 弹性模量与阳极氧化制 备 的 多 孔 硅 材 料 机 械 性 能 相 近 . 结 构 耐 热 性 方 面 , Umemura 等人 [37] 发现舟形藻壳体在 800℃加热 2 h 后 结构与微孔变形. 可加工性方面, SiO 2 壳体能与强碱 和氢氟酸反应, 兼容硅加工工艺, 如湿法刻蚀、LIGA 体微加工、硅键合等.…”
unclassified